Anaerobic treatment of wastewater generated from meat processing industry using up flow anaerobic sludge blanket (UASB) reactor - Natsheh, Asma; Gazzar, Sanabel (جامعة بوليتكنك فلسطين - كلية الهندسة - بيئة, 2017)
meat processing industry generates wastewater with relatively low levls of organic pollutants expressed as chimical oxygen demand ( COD ) and the total suspended solids ( TSS ) in addition to other pollutants like ammonia nitrogen an organic nitrogen. according to the initial chemical analysis conducted by seniora company on mar,25/2017 , the COD, TSS , ammonia nitrogen and total nitrogen concentration was found to be 2243 , 760,2.6 and 149.1,mg/l respectively.
CD,30301 , no of pages 45 , 13/2017بيئة , in the store